2000
DOI: 10.1007/s001140050015
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Hair Cell Turnover in the Inner Ear Vestibular Organs of a Mammal, the Daubenton's Bat ( Myotis daubentonii )

Abstract: In both humans and mice the number of hair cells in the inner ear sensory epithelia declines with age, indicating cell death (Park et al. 1987; Rosenhall 1973). However, recent reports demonstrate the ability of the vestibular sensory epithelia to regenerate after injury (Forge et al. 1993, 1998; Kuntz and Oesterle 1998; Li and Forge 1997; Rubel et al. 1995; Tanyeri et al. 1995). Still, a continuous hair cell turnover in the vestibular epithelia has not previously been demonstrated in mature mammals. Bats are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…A diagram of this cell (L) also shows a GFP + nonsensory cell and two GFP + support cells surrounding the hair cell. Steyger et al 1997), chicks (Raphael et al 1994Adler and Raphael 1996;Adler et al 1997), bats (Kirkegaard andJorgensen 2000), and guinea pigs (Li and Forge 1997). Since hair cell regeneration occurs in most vertebrate species, it is perhaps unsurprising that these different species show similar changes as cells transition between the distinct morphologies of support cells and hair cells.…”
Section: Fig 8 Examples Of Lineage Traced Transitional Cells (Tc) mentioning
confidence: 99%
“…A diagram of this cell (L) also shows a GFP + nonsensory cell and two GFP + support cells surrounding the hair cell. Steyger et al 1997), chicks (Raphael et al 1994Adler and Raphael 1996;Adler et al 1997), bats (Kirkegaard andJorgensen 2000), and guinea pigs (Li and Forge 1997). Since hair cell regeneration occurs in most vertebrate species, it is perhaps unsurprising that these different species show similar changes as cells transition between the distinct morphologies of support cells and hair cells.…”
Section: Fig 8 Examples Of Lineage Traced Transitional Cells (Tc) mentioning
confidence: 99%
“…Small HCs have been described in the inner ear vestibular sensory epithelia of all vertebrates examined (Jørgensen 1970(Jørgensen , 1975Li 1973, 1975;Corwin 1983;Mathiesen 1985;Rubel et al 1995;Kirkegaard and Jørgensen 2000). It has also been observed that the stereovilli of small HCs are thinner than stereovilli on normal-sized HCs (Jørgensen 1970(Jørgensen , 1975Mathiesen 1985;Kirkegaard and Jørgen-sen 2000).…”
Section: Formation Of New Hcs In the Ummentioning
confidence: 99%
“…Details concerning the architectural mechanisms which govern the apical development of small HCs with thin stereovilli have been given by Tilney et al (1992). Furthermore, a TEM study on Daubenton's bat Myotis daubentonii has revealed that the small HCs are basally innervated (Kirkegaard and Jørgensen 2000). These observations, together with the fact that apoptotic HCs have been observed in representatives of all other vertebrate classes (Jørgensen 1981;Jørgensen and Mathiesen 1988;Jørgensen and Locket 1995;Kirkegaard and Jørgen-sen 2000;Jensen and Jørgensen 2001), strongly indicate that small HCs are early stages of functionally mature ones.…”
Section: Formation Of New Hcs In the Ummentioning
confidence: 99%
“…For example, studies suggest that bats may be able to generate new hair cells within certain regions of the inner ear after birth (Kirkegaard and Jørgensen 2000); although the functional impact of this on their sensory perception remains unclear. The particular diets of bat species may be either high in fats or sugars, yet bats appear to avoid the associated health implications such as artherosclerosis or hyperglycemia (Widmaier et al, 1996;Brunet-Rossinni and Austad 2004;Mqokeli and Downs 2012) which are frequently seen in ageing human populations.…”
Section: Introductionmentioning
confidence: 99%